Segmenting wine markets with diverse price functions: Evidence from California red and white wines sold in British Columbia - Richard Carew; Wojciech J. Florkowski; Ting Meng (Wine Economics and Policy, 2017)
Previous hedonic price studies on wine market segments, exploring diverse price functions, are constrained by pre-determined price breakpoints, the total number of segments, or both. Using British Columbia Liquor Distribution Branch (BCLDB) retail price data of California red and white wines, this study adopts an endogenous approach to explore the total number of market segments and identify breakpoints in price dispersion simultaneously. Results show that red and white California wines are grouped into two (breaking at Can 14 per bottle) and three (breaking at Can 16 and 30 per bottle) price segments, respectively. Also, implicit prices of wine attributes such as grape variety and geographic origin differ for red and white wines across market segments.
Keywords: 330; Hedonic; Segmentation; Wine